Neuroprotective Effects of Quercetin and Rutin on Spatial Memory Impairment in an 8-Arm Radial Maze Task and Neuronal Death Induced by Repeated Cerebral Ischemia in Rats - Fengling Pu; Kenichi Mishima; Keiichi Irie; Kyouko Motohashi; Yurika Tanaka; Kensuke Orito; Takashi Egawa; Yoshihisa Kitamura; Nobuaki Egashira; Katsunori Iwasaki; Michihiro Fujiwara (Elsevier, 2007)
In order to determine the differential effects of flavonoids on cerebral ischemia, we investigated the effects of (−)-epigallocatechin gallate (EGCG), catechin, rutin, and quercetin on spatial memory impairment and neuronal death induced by repeated cerebral ischemia in rats. Both rutin and quercetin (50 mg/kg × 2) improved spatial memory impairment in the 8-arm radial maze task and neuronal death in the hippocampal CA1 area; however, catechin (200 mg/kg × 2) and EGCG (50 mg/kg × 1) did not. Administration of EGCG (50 mg/kg × 2) resulted in a high mortality rate. These results suggest that in this repeated cerebral ischemia model, the 4-oxo group and the 2,3-double bond in the C ring of rutin and quercetin are related to their neuroprotective action. Keywords:: (−)-epigallocatechin gallate (EGCG), catechin, rutin, quercetin, repeated cerebral ischemia model